KARAKTER ORANG MADURA DAN FALSAFAH POLITIK LOKAL - Ainurrahman Hidayat (Institut Agama Islam Negeri Madura)
Abstrac This article attempts to explore the basic character of Madurese people that put the moral-ethic basics on every attitude, utterances, and behavior of Madurese local politic phenomena. The study results four basic characteristics of Madurese—ejhin, koko, gherra and saduhunah. Those become local wisdom of Madurese people. The four basic characters should have introduced and provided each Madurese local politic phenomena to reach a better politic life. Ejhin character carries a tolerant nature, friendship and dependent. Koko character introduces loyality, consistency, trust and responsibility. Gherra character reflects carefulness, transparency, and fairness. Saduhunah describes honesty and innocent. Kata-kata kunci ejhin, gherra, koko, saduhuna